Web based ETL Approach to Transform Relational Database to Graph Database - Sonali D, Chaure; Kulkarni, MU; Pankaj M, Jadhav (International Journal of Computer Sciences and Engineering, 2025)
Data size is growing exponentially, it is coming in more and more connected form. Graph Database Management System (GDBMS) provides efficient solution to data storage in current scenarios. Nowadays, many companies rely on cloud services where you pay as per your need basis and most of the cloud platforms supports non-relational database to avoid scalability issues. Graph Databases have applications in many domains such as social network, organization management, banking, insurance, fraud detection, etc. Therefore there is need to migrate data from relational to non-relational database. Also many companies shifting from traditional relational database to NoSQL databases to avoid scalability issues. In this paper a web based ETL approach has been suggested to convert a Relational Database to Graph Database. Experimental results have been presented to show feasibility of the proposed methodology. Also query execution comparison is done on source and target databases.